Primary Mediastinal Synovial Sarcoma Presenting as Superior Vena Cava Syndrome: A Rare Case Report and Review of the Literature. (25th May 2015) - Madabhavi, Irappa; Kataria, Pritam; Patel, Apurva; Revannasiddaiah, Swaroop; Anand, Asha; Panchal, Harsha; Parikh, Sonia; Sarkar, Malay; Modi, Gaurang; Kulkarni, Rahul; Shah, Sandip
Abstract : Primary mediastinal sarcomas are aggressive tumors with a very rare incidence. This report describes the case of a 35-year-old male patient who presented with acute symptoms of dyspnoea, facial puffiness, voice-hoarseness, and engorged neck veins. With the clinical picture consistent with the superior vena cava (SVC) syndrome, the patient was investigated with computed tomography of the chest. This revealed a large soft tissue density mass lesion compressing the SVC along with other critical superior mediastinal structures. Histopathological evaluation of the mass revealed features consistent with a soft tissue sarcoma and positive staining was observed for vimentin and S-100. Cytogenetic analysis by fluorescent in situ hybridisation (FISH) demonstrated the t(X:18) translocation. Thus diagnosis was established as primary mediastinal synovial sarcoma. Patient was treated with three cycles of neoadjuvant chemotherapy, to which there was a partial response as per the RECIST criteria. Surgical excision of the mediastinal mass was performed, and further postoperative treatment with adjuvant chemoradiotherapy was provided. Patient currently is free of disease. This is to the best of our knowledge the first report in the world literature of a successfully treated case of "primary mediastinal sarcomas presenting as SVC syndrome." Patient is under regular surveillance at our clinic and remains free of recurrence one year after treatment completion.